Role of computed tomography and MRI in children with sensorineural hearing loss - Ahmad Mohamed Saeed Alkady; Saad Rezk Abd Al-Wa; Tarek Mohamed Mohamed Mansour; Mohamed M Elmoursy Kasem (Wolters Kluwer Medknow Publications, 2022)
Background and aim Given the tremendous developments in visualization science, there are many congenital and acquired internal ear anomalies that have no radiological signs. However, visualization is an important instrument for the assessment of congenital and acquired sensory neural hearing loss (SNHL) triggers. The aim is to assess the value of multidetector computed tomography (MDCT) and MRI in internal ear abnormality detection in children with SNHL. Patients and methods This study included 100 children of 10 years or younger with SNHL. The cochlea, the vestibule, the three semicircular canals, the endolymphatic duct, and the internal acoustic canal. In addition, three-dimensional DRIVE MRI gives good demonstration of all four nerves within the internal acoustic canal. Results A total of 46 malformations were detected in only 25 patients with 42 malformations that were detected in MDCT examination presenting 91% of all abnormalities, while in MRI examination, 44 malformations are detected presenting 96% of all abnormalities. MDCT showed accuracy, sensitivity, and specificity 96.7, 91.3, and 100%, respectively, while for MRI, it showed accuracy, sensitivity, and specificity 98.3, 95.7, and 100%, respectively. Conclusion Imaging plays an important role in the workup of children with SNHL. Therefore, it is imperative to define the etiology of hearing loss. High-resolution CT and MRI modalities are the two principal radiological investigations to detect various pathologies in the inner ear. 'Dual-modality imaging' using both MRI and CT, made sense for many patients because the dual-scan approaches detect abnormalities related to hearing loss that would not otherwise be found using either modality alone.